Evaluation of the protective effect of edaravone on doxorubicin nephrotoxicity by [99mTc]DMSA renal scintigraphy and biochemical methods - Demir, Fadime; Demir, Mustafa; Aygun, Hatice (Springer, 2020)
To evaluate the nephroprotective effect of edaravone on doxorubicin-induced nephrotoxicity. In this experimental study, twenty-eight Wistar male rats were used. The rats were separated into 4 groups (n = 7); group CYRILLIC CAPITAL LETTER BYELORUSSIAN-UKRAINIAN I (control), rats were treated with saline (4 ml/kg) and group CYRILLIC CAPITAL LETTER BYELORUSSIAN-UKRAINIAN ICYRILLIC CAPITAL LETTER BYELORUSSIAN-UKRAINIAN I (doxorubicin), nephrotoxicity was induced by three doses of 18 mg/kg/i.p. doxorubicin, at a 24-h interval on the 12th, 13th, and 14th days. Group CYRILLIC CAPITAL LETTER BYELORUSSIAN-UKRAINIAN ICYRILLIC CAPITAL LETTER BYELORUSSIAN-UKRAINIAN ICYRILLIC CAPITAL LETTER BYELORUSSIAN-UKRAINIAN I (edaravone), rats were treated with edaravone (30 mg/kg/for 14 days), and group CYRILLIC CAPITAL LETTER BYELORUSSIAN-UKRAINIAN IV (edaravone + doxorubicin), rats were treated with edaravone (30 mg/kg/for 14 days) and doxorubicin were injected (18 mg/kg/for 3 days; at a 24-h interval on the 12th, 13th, and 14th days). On the 15th day of the experiment, technetium-99m-labeled dimercaptosuccinic acid ([Tc-99m]DMSA) uptake was obtained in both kidneys and biochemical parameters from serum and kidney tissue were measured. Doxorubicin led to nephrotoxicity through elevation of serum blood urea nitrogen (BUN), creatinine and tumor necrosis factor-alpha (TNF-alpha), nitric oxide (NO), and interleukin-6 (IL-6) in kidney tissue and decreased [Tc-99m]DMSA uptake level in the kidney when compared with control group (p < 0.01). Pretreatment edaravone significantly decreased BUN and creatinine, also kidney tissue TNF-alpha, IL-6, NO, and increased [Tc-99m]DMSA uptake level compared with the doxorubicin. Edaravone has a significant nephroprotective effect through the attenuation of oxidative stress and inflammatory markers during doxorubicin-induced nephrotoxicity in rats.
Keywords: Edaravone; Doxorubicin; Nephrotoxicity; [Tc-99m]DMSA; TNF-alpha; IL-6; NO